Creation of a Unified Transport and Logistics Platform as a Factor of Dgitalization of the Transport Sector of the Republic of Belarus - Yu. P. Yakubuk (Цифровая трансформация, 2025)
Digital transport and logistics platforms are becoming increasingly widespread in the global eco nomy, contributing to an increase in the volume of supplies of goods and simplifying interaction between shippers, consignees, carriers, government agencies and other participants in the transportation process. The state prog ram “Digital Development of Belarus” for 2021–2025 provides for the development of an integration platform for the national electronic logistics system. The article examines the development of conceptual provisions for the creation of the Unified Transport and Logistics Platform of Belarus, including the goals of its creation, principles of development and implementation, basic elements, the need to take into account and resolve problematic issues, and a generalized composition of the functional services of the platform. In contrast to the developments of digital transport platforms presented in the Belarusian information space, it is proposed to unite on one platform all parti cipants of the Belarusian transport industry (transport and logistics companies and other carriers, logistics centers, shippers and consignees, vehicle owners, passengers) and entities directly and indirectly influencing transportation processes (government agencies, automated information systems), as well as to ensure the possibility of integra tion with digital platforms of other countries (EAEU, China).